2014
DOI: 10.1016/j.ultras.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring tissue inflammation and responses to drug treatments in early stages of mice bone fracture using 50MHz ultrasound

Abstract: Bone fracture induces moderate inflammatory responses that are regulated by cyclooxygenase-2 (COX-2) or 5-lipoxygenase (5-LO) for initiating tissue repair and bone formation. Only a handful of non-invasive techniques focus on monitoring acute inflammation of injured bone currently exists. In the current study, we monitored in vivo inflammation levels during the initial 2 weeks of the inflammatory stage after mouse bone fracture utilizing 50 MHz ultrasound. The acquired ultrasonic images were correlated well wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…Our recent publication 21 suggests that the increases in echogenicity in injured bone are positively correlated to tissue inflammatory responses, particularly COX-2- or 5-LO-mediated signal pathways. In the present study, immunohistological staining revealed significant increases in protein expression of COX-2, but not BLT1 (receptor of leukotriene B4 for 5-LO signaling), in the venous endothelium at 3 weeks after surgery ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent publication 21 suggests that the increases in echogenicity in injured bone are positively correlated to tissue inflammatory responses, particularly COX-2- or 5-LO-mediated signal pathways. In the present study, immunohistological staining revealed significant increases in protein expression of COX-2, but not BLT1 (receptor of leukotriene B4 for 5-LO signaling), in the venous endothelium at 3 weeks after surgery ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S2A ). The HFU system comprised of a 30-MHz transducer was used to generate and receive ultrasound signals as described in a previous study 21 . The series of cross-sectional images were acquired to monitor the dynamic changes in vascular structures from proximal to distal sites of vessels with 50-μm intervals at post-surgery weeks 1, 2, and 3 (W1, W2, W3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Echogenicity increases with increasing density and with decreasing homogeneity [ 16 ]. Our recent findings suggest that echogenicity can also be used as an indicator for tissue inflammation during fracture healing [ 17 ]. Numerous studies have examined backscattered signals analyzed by Nakagami distribution analysis in ultrasonic pulse-echo images; these studies have found that the signals reflect the structure of the tissue and can predict tissue composition and complexity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Nakagami parameter has been widely used in soft-tissue characterization of, for example, cataracts26, blood27, liver2829, breast30, and thrombus31. The Nakagami parameter is also used in modeling the echo amplitude distribution of bony tissues3233. Therefore, we assumed that the Nakagami parameter can quantify the acoustic structure of the mastoid and correlated it with clinical MEE.…”
mentioning
confidence: 99%